Burden of cytomegalovirus disease in solid organ transplant recipients: a national matched cohort study in an inpatient setting. Issue 5 (21st July 2017) - Hakimi, Zalmai; Aballéa, Samuel; Ferchichi, Sameh; Scharn, Micky; Odeyemi, Isaac A.; Toumi, Mondher; Saliba, Faouzi
Abstract: Background: We investigated the impact of early‐ (E‐CMV) and late onset (L‐CMV) cytomegalovirus disease on the probability of graft rejection, graft failure, mortality, and healthcare resource use, following solid organ transplantation (SOT) in France. Methods: A retrospective analysis of data from the French 'Programme de Médicalisation des Systèmes d'Information' database (2007‐2011) was conducted to identify SOT recipients who developed CMV disease in an inpatient setting. Recipients were stratified by time to CMV disease onset: E‐CMV (≤3 months), L‐CMV‐3M (>3‐24 months), and L‐CMV‐6M (>6‐24 months). Data were analyzed by comparing recipients with CMV disease or without (controls) in a 1:2 ratio, matched according to age, gender, target organ, and previous/simultaneous occurrence of graft rejection. Graft failure, graft rejection, all‐cause in‐hospital mortality, and resource utilization (including hospitalization costs) were assessed over 12 months following CMV disease diagnosis. Results: Among 20 473 SOT recipients, 2430 (11.86%) were reported to have CMV disease within 24 months after transplantation. CMV disease was significantly associated with an increased risk of graft rejection and mortality, as indicated by logistic regression analysis. Odd ratios (ORs) for the risk of graft rejection were E‐CMV=1.43, L‐CMV‐3M=1.50, and L‐CMV‐6M=1.61 (all P <.05), while ORs for mortality were E‐CMV=2.85, L‐CMV‐3M=4.22, and L‐CMV‐6M=4.77 (all P <.0001). Only L‐CMV was significantly correlated with a higher risk of graft failure: E‐CMV=1.18 ( P= .1906), L‐CMV‐3M=1.77 ( P= .0013), and L‐CMV‐6M=3.12 ( P <.0001). Hospitalization costs increased by €7078 (range €6270‐€22 111), €6523 (range €5328‐€10 295), and €6311 (range €5295‐€9184) in recipients with E‐CMV, L‐CMV‐3M, and L‐CMV‐6‐M, respectively. Conclusion: This study, based on French national data, demonstrates the considerable burden of CMV disease in SOT recipients and highlights the importance of developing new strategies to prevent and manage CMV disease and improve clinical outcomes for SOT patients.